CONSUMER PERCEPTION OF GREEN MARKETING STRATEGY ON PURCHASE INTENTION IN AMUNTAI, HULU SUNGAI UTARA REGENCY - Haris Fadillah (PPPM STIA Amuntai, 2025)
This study aims to explore consumer perceptions of green marketing strategies and to what extent these strategies influence purchase intention toward sustainable products in Amuntai, Hulu Sungai Utara Regency. The research is grounded in the growing awareness of environmental issues such as pollution, climate change, and plastic waste, which have prompted businesses to adopt environmentally friendly marketing approaches. A descriptive qualitative method was employed, utilizing in-depth interviews, participatory observation, and documentation as data collection techniques. The findings reveal that several local SMEs have started implementing elements of green marketing, such as using eco-friendly materials and promoting environmental education through their marketing channels. Consumers in this region—especially young adults and environmentally conscious households—are showing a growing interest in sustainable products, particularly those with natural ingredients, eco-friendly packaging, and clear environmental messaging. However, significant challenges remain, including limited knowledge among business owners, higher production costs, and a lack of local government support. The study concludes that green marketing holds substantial potential to increase consumer purchase intention, yet it requires a more structured, collaborative, and educational approach. These findings offer strategic insights for local SMEs, government stakeholders, and community groups seeking to advance sustainable business practices in the region.